The Impact of Working Capital, Inventory, and Total Assets on Net Profit (A Study on Trading Companies in The Retail Sub-Sector Listed on The Indonesia Stock Exchange for the Period 2017-2024) - Victoria, Shena; Damayanti, Santi; Kosadi, Ferry (Jurnal Indonesia Sosial Sains, 2026)
Finding and explaining the impact of working capital, inventory, total assets, and sales on net profit is the primary goal of this study. This data is derived from secondary sources found in IDX. Within the Financial Statement Period 2017–2024, the sample population consists of 31 retail trade subsector companies registered on the Indonesia Stock Exchange. For the sample, four different firms were chosen. Nonprobability sampling is the basis of this method's purposeful sample approach. The quantitative research methodologies employed in this study are both descriptive and verifiable. Standard deviation, mean, minimum, and maximum are the four pillars upon which descriptive statistics rest. Four parts make up verifiable statistical analysis: the determination coefficient, the product-moment correlation coefficient, the classical assumption test, and multiple linear regression. The t-test and the f-test are the two ways that hypotheses may be tested. Working Capital (X1) has a positive effect on net profit (t-value: 3.930, exceeding ttable: 2.045, and p-value: less than 0.05), while Inventory (X2) has a similar effect (t-value: 2.156, exceeding ttable: 2.045, and p-value: less than 0.05), according to the t-test for partial hypotheses. the third With a significance level below 0.050 and an estimated t value of -2.597 (smaller than the table t value of -2.045), Total Assets (X3) have a negative effect on Net Profit. The outcomes of Working Capital, Inventory, and Total Assets all had an impact on Net Profit at the same time, according to the findings of the simultaneous hypothesis test (f-test). With a GIS value of less than 0.001, an FCount of 24.913 was obtained.